A Survey on Facial Age Estimation Techniques - Verma, Vishnu Prasad; Verma, Dipti (International Journal of Computer Sciences and Engineering, 2025)
Age Estimation is predicting a person’s age and is a very important attribute used for identity authentication. One of the major factors affecting the age estimation result is the identification of features of a person’s face accurately. Age Estimation has several real-world applications, equivalent to security management, biometrics, client relationship management, recreation, and cosmetology. The foremost ordinarily used age estimation technique is regression based mostly as a result of it takes into consideration the interrelationship among the age values for face pictures. The current work is an overview of techniques employed previously for age estimation.